Normative Types of Journalism and Reporting on Policy trough the Optics of Slovenian Journalists, Politicians and Citizens - Vobič, Igor (Javnost-The Public, 2009)
The article examines social specifi city of normative assumptions of journalism through the lenses of journalists, politicians and citizens with an emphasis on contemporary political, economic and cultural dynamics in Slovenian journalism and media environment. Literature review reveals fi ve normative types of journalism, in terms of the kind of service journalists provide to the clients and primary functions of journalists in the society: meditative, advocacy, enlightenment, entertainment and communitarian journalism. The text frames the debate on types of journalism by (re)considering profound changes in the relationship between state, civil society and media in Slovenia after adoption of Western-type democracy and market economy two decades ago, which have transformed normative grounding of journalism, relationship between journalists, politicians and citizens and their functions in political life and journalism. The main research objectives of the article are to identify perceptions of surveyed Slovenian journalists, politicians and citizens on journalists’ functions in reporting on politics, examine the diff erences between these groups of respondents in politically, economically and culturally specifi c context of media and journalism, and refl ect on contemporary status of journalism and journalists in politics through the prism of normative types of journalism.